PENGARUH KARAKTERISTIK PEMERINTAH DAERAH DAN TEMUAN PEMERIKSAAN BPK TERHADAP KINERJA PEMERINTAH DAERAH KABUPATEN/KOTA DI INDONESIA TAHUN ANGGARAN 2012 - Rizal Qowi; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2017)
This study aims to prove that the level of wealth, dependence to the central government, capital expenditure of local government, and the audit finding of BPK, are influential for performace of local governments of Indonesia in 2012 . The performance is measured by scores in the EPPD’s evaluation report that arranged nationally by Ministry of Home Affairs. Population of this research is whole of Indonesia’s local governments in 2012. Total of samples are 477 local governments that consist of 384 regencies and 93 cities. This research uses purposive sampling method and SPSS 21 software as the analysis program. The result shows that the level of wealth of local government has positif effect for it’s performance, but the level of dependence to the central government, the level of capital expenditure, and the audit finding of BPK have negatif effect for it’s performance.